Adenosquamous carcinoma in the palate of a dog: case report - Gomes, Ana Laura Paulino Leite; Nóbrega, Daniela Farias da; Azzem, Patrícia Bruder; Bruder, Dóris; Bracarense, Ana Paula Frederico Rodrigues Loureiro (Brazilian Journal of Veterinary Pathology, 2022)
Adenosquamous carcinoma is characterized by the simultaneous presence of squamous and glandular components. This article reports a case of adenosquamous carcinoma in the oral mucosa in a dog. Microscopically, the tumour revealed an infiltrative epithelial proliferation with a tubular pattern and areas of squamous differentiation. In the lumina of the tubules, there were eosinophilic material (mucin). The alcian blue staining showed positive intraluminal material and the cytoplasm of neoplastic cells were immunoreactive for cytokeratin, supporting the diagnosis of adenosquamous carcinoma. The cells exhibited reduced or negative immunoreactivity for E-cadherin, which could be associated with more aggressive tumour behaviour and worse prognosis.